SYSTEMATIC LITERATURE REVIEW (SLR): PENGUKURAN KINERJA PADA SEKTOR PENDIDIKAN MENGGUNAKAN BALANCED SCORECARD - D. Febry Wulangsih; Saniya Mahira Salma; Luthfi Azmi Sa’diyah; Anita Wulansari (Cattleya Darmaya Fortuna, 2024)
A Balanced Scorecard (BSC) can be used to measure how the learning process of students or the improvement of employee abilities or competencies. To know where the location needs to be improved. In addition, it is easier to set the goals of education itself. Some educational institutions, such as formal and non-formal schools and universities, have implemented the Balanced Scorecard (BSC). System Literature Review (SLR) is an independent academic method. It aims to identify and evaluate all relevant literature to reach conclusions about the questions the author asks or wants to know. The results explain that the Balanced Scorecard (BSC) measurement is very beneficial in evaluating education in financial, internal business, customer, and learning aspects.